IN-SILICO STUDY OF ACETYLCHOLINESTERASE INHIBITION BY ORGANOPHOSPHATE PESTICIDES - MADHULIKA CHAUDHRY; J. FEBIN PRABHU DASS; D.SELVAKUMAR; DR. N.S.KUMAR (International Journal of Pharma and Bio Sciences, 2013)
Pesticides are widely used round the globe for a plethora of applications that vastly includes agricultural fields and commercial gardens. Despite their wide use that aid increase in crop yield, they have ill-effects on environment and non-target organisms. Organophosphates (OP) are an important class of pesticides, which cause irreversible inhibition of acetylcholinesterase (AChE). Irreversible inhibition of AChE may lead to severe pathological conditions such as muscular paralysis, bronchial constriction and even death by asphyxiation. An in-silico approach was employed to study the interaction of AChE with four commonly used OP pesticides namely, methyl parathion, dichlorvos, malathion, chlorpyrifos. AutoDock4.2 and iGEMDOCK and SwissDock are opensource docking tools which were used to form the AChE-OP complex. Further these complexes were explored on their protein-ligand binding affinity along with the mechanism of binding. Based on the results, It was found that chlorpyrifos has the best binding affinity with AChE as compared to the other pesticides. These observation would surely be helpful in development of precautionary antidotes for the people who have direct contact with these poisonous pesticides. In addition, this information may be utilized in developing non-toxic therapeutic leads from the best binding pesticides, for Alzheimer’s diseases, where AChE is considered as a potential drug target.